Multiple recurrences in Pityriasis rosea - A case report with review of the literature - Senthilkumar Sankararaman; Sujithra Velayuthan (Wolters Kluwer Medknow Publications, 2014)
Pityriasis rosea (PR) is a common benign cutaneous disorder of children and young adults. The etiology of this condition is still unknown. Despite the common occurrence, second episode of PR is noted only in 1-3% of the cases. Multiple recurrences (three or more episodes) are extremely uncommon and to the best of our knowledge, only few patients have been reported in the literature. Due to the benign nature of the disease, these recurrences may be either underestimated or unreported. Till date, there are no predisposing factors identified for the occurrence of these multiple episodes. We report a case of pityriasis rosea in an 11-years-old male with three episodes with review of the literature.